2020
DOI: 10.1155/2020/4795171
|View full text |Cite
|
Sign up to set email alerts
|

Engineered IL-7 Receptor Enhances the Therapeutic Effect of AXL-CAR-T Cells on Triple-Negative Breast Cancer

Abstract: Triple-negative breast cancer (TNBC) is a very aggressive malignant type of tumor that currently lacks effective targeted therapies. In hematological malignancies, chimeric antigen receptor T (CAR-T) cells have shown very significant antitumor ability; however, in solid tumors, the efficacy is poor. In order to apply CAR-T cells in the treatment of TNBC, in this study, constitutively activated IL-7 receptor (C7R) that has been reported is used to enhance the antitumor function of constructed CAR-T cells by our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 34 publications
(30 reference statements)
1
51
0
Order By: Relevance
“…Therefore, C7R had a unique ability to provide signal 3 only to CAR T cells, without affecting bystander lymphocytes. In addition, C7R expression can significantly improve the activation, proliferation, and persistence of CAR T cells, to effectively eliminate triple-negative breast cancer cells [86].…”
Section: Constitutive Il-7 Cytokine Receptor Signalingmentioning
confidence: 99%
“…Therefore, C7R had a unique ability to provide signal 3 only to CAR T cells, without affecting bystander lymphocytes. In addition, C7R expression can significantly improve the activation, proliferation, and persistence of CAR T cells, to effectively eliminate triple-negative breast cancer cells [86].…”
Section: Constitutive Il-7 Cytokine Receptor Signalingmentioning
confidence: 99%
“…In addition, since AXL expression is found on MDSCs, it is possible that CAR-T cells targeting AXL may deplete MDSCs from the TME and fundamentally alter the TME to a proinflammatory state (69). More recently, it was demonstrated that AXL-CAR-T cells with constitutive expression of the IL-7 receptor had enhanced in vitro anti-tumor activity and prolonged survival in a TNBC subcutaneous xenograft model (70). Collectively, these data underscore the importance of AXL as a novel CAR-T cell therapy target in TNBC and its potential to polarize the TME to a pro-inflammatory state conducive for effective anti-tumor immune responses.…”
Section: Receptor Tyrosine Kinase Axlmentioning
confidence: 99%
“…Chimeric antigen receptor T (CAR-T) therapy shows important antitumor effects in patients with hematological malignancies but still remains ineffective in solid tumors. In vitro and in vivo experiments conducted in TNBC cells have shown encouraging results in terms of the antitumor activity of AXL-targeting CAR-T, confirming the real potential of this new therapeutic approach [ 106 ]. The promising results obtained in the preclinical field have led to the introduction of the pharmacological combination between AXL inhibitors and immunotherapy in various tumor contexts, including breast cancer, to bypass innate resistance.…”
Section: Axl Implications In Breast Cancersmentioning
confidence: 96%